Simulium (Gomphostilbia) sofiani, a New Species of Black Fly (Diptera: Simuliidae) from Peninsular Malaysia - Takaoka, H.; Sofian-Azirun, Mohd; Hashim, R. (Malaysian Society of Parasitology and Tropical Medicine, 2011)
Simulium (Gomphostilbia) sofiani sp. nov. is described on the basis of reared adult female, male, pupal and larval specimens collected from Cameron Highlands, Pahang state, Malaysia. This new species is placed in the ceylonicum species-group within the subgenus Gomphostilbia and is easily distinguished from all the related known species by the combination of the following characteristics: an elongate sensory vesicle and yellow hair tuft on the stem vein of the wing in the female, the greater number of large upper-eye facets (15 or 16 vertical columns and 15 or 16 horizontal rows) and almost entirely darkened hind basitarsus in the male, and the gill bearing a long common basal stalk and 8 filaments arranged as (1+2)+ (1+2) +2 filaments from dorsal to ventral in the pupa.